Persepsi Hambatan dan Preferensi Mahasiswa terhadap Pembelajaran Daring di Masa Pandemi Covid-19 - Mohammad Rizal Gaffar; Sri Surjani (al-fikrah: Jurnal Manajemen Pendidikan, 2021)
All Colleges implemented online learning after Covid-19 was declared as a pandemic in Indonesia. Still, only a few collegesget used to it. Many factors can be  barriers to reach learning objectives. This study aims to describe the condition of students at one of the Colleges in Bandung using mixed-methods with development type. The first step wasthe spreading of  a questionnaire via a short message application. As many as 153 respondents filled in the questionnaire from whom the  data of the research were obtained and used. Data from the questionnaire were, then,  processed and formed into several diagrams. After that, confirmation regarding the results of the diagram was carried out on several respondents to findtheir insight of what barriers that were actually felt by students. The results showed that the main barriers felt by studentsare  regarding internet quotas. Lecturers need to design the most efficient and effective learning model so that learning objectives can be reached with all of the limited resources.